Cyprus in texts from Graeco-Roman antiquity - Carvounis, Katerina,Gavrielatos, Andreas,Karla, Grammatikē,Papathōmas, Amphilochios (Brill, 2023)
How was the unique character of the island of Cyprus perceived in antiquity? This volume aims to engage with this question by examining references to Cyprus in ancient texts and by exploring authors connected to the island. The readers can thus find literary interpretations on a wide range of Greek and Latin texts focusing on Cyprus by world-leading Classical scholars, which will cast further light on the literary and cultural tradition of the island. The book promises to motivate further exploration of these topics and of the influence of a place in ancient literature and beyond
Enthält Literaturangaben
Keywords: Aufsatzsammlung; Classical literature / History and criticism; Cyprus / In literature